Г. Владимов, Вен. Ерофеев, В. Маканин, А. Ким, М. Рощин, А. Приставкин, М. Кураев, Е. Попов, Л. Петрушевская, Т. Толстая - Басинский П. В. (2000)
Экземпляры: (20200204) / Инвентарный номер: 37321 / Цена: / Сис.шифр: 84Р6 / Авт.знак: П 79 / ББК: 84(2Рос=Рус)6